Review of / Reseña de: Guirao Mirón, Cristina. Transgresoras. Una historia cultural de las mujeres. Madrid: Catarata, 2024. 109 pp. ISBN: 978-84-1067-045-7 - Laura Linares Abadía (Feminismo/s)
Review of / Reseña de: Guirao Mirón, Cristina. Transgresoras. Una historia cultural de las mujeres. Madrid: Catarata, 2024. 109 pp. ISBN: 978-84-1067-045-7